ASS1 deficiency is associated with impaired neuronal differentiation in zebrafish larvae - Seidl, Marie; Scharré, Svenja; Posset, Roland; Druck, Ann-Catrin; Epp, Friederike; Okun, Jürgen G.; Dimitrov, Bianca; Hoffmann, Georg F.; Kölker, Stefan; Zielonka, Matthias (Molecular genetics and metabolism, 2024)
Citrullinemia type 1 (CTLN1) is a rare autosomal recessive urea cycle disorder caused by deficiency of the cytosolic enzyme argininosuccinate synthetase 1 (ASS1) due to pathogenic variants in the ASS1 gene located on chromosome 9q34.11. Even though hyperammenomia is considered the major pathomechanistic factor for neurological impairment and cognitive dysfunction, a relevant subset of individuals presents with a neurodegenerative course in the absence of hyperammonemic decompensations. Here we show, that ASS1 deficiency induced by antisense-mediated knockdown of the zebrafish ASS1 homologue is associated with defective neuronal differentiation ultimately causing neuronal cell loss and consecutively decreased brain size in zebrafish larvae in vivo. Whereas ASS1-deficient zebrafish larvae are characterized by markedly elevated concentrations of citrulline - the biochemical hallmark of CTLN1, accumulation of L-citrulline, hyperammonemia or therewith associated secondary metabolic alterations did not account for the observed phenotype. Intriguingly, coinjection of the human ASS1 mRNA not only normalized citrulline concentration but also reversed the morphological cerebral phenotype and restored brain size, confirming conserved functional properties of ASS1 across species. The results of the present study imply a novel, potentially non-enzymatic (moonlighting) function of the ASS1 protein in neurodevelopment.